Uji Kandungan Vitamin C dan Organoleptik Dodol Terung Belanda (Solanum betaceum) - Dewa Gede Eka Sastra Wiguna; Suyastini Ni Komang; Suka Widana I Nengah; Sumaryani N.Putri (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
Dodol is a popular traditional food, known since ancient times. The addition of terung belanda(Solanum betaceum) in making dodol can increase the economic value of terung belanda. The purpose of this study was to determine the vitamin C and organoleptic content based on color, texture, aroma and taste in dodol terung belanda. The data is in the form of quantitative data about the content of vitamin C and organoleptic dodol terung belanda, the data was obtained by observation and questionnaire. Data on vitamin C content in dodol, using the titimetry method with dye or idophenol solution, was carried out in the Laboratory Service Unit of the Faculty of Agricultural Technology, Udayana University. Organoleptic test data were analyzed by descriptive percentage.Tests for vitamin C content in dodol terung belanda showed a value of 14.05 mg / 100g of ingredients, while those of terung belanda were 22.08 mg / 100g of ingredients. The content of vitamin C in dodol decreased by 8.03 mg (36.45%). The rate of reduction in vitamin C content is meaningless (negligible). Organoleptic tests showed scores obtained based on dodol color, namely 75% likes, dodol texture 78.75% likes, dodol 83.75% very likes and dodol which is 90% with very like category. The average organoleptic test results from 4 components showed a very like category (81.87%).